Feasibility of Neoadjuvant Ad‐REIC Gene Therapy in Patients with High‐Risk Localized Prostate Cancer Undergoing Radical Prostatectomy. Issue 6 (1st December 2015) - Kumon, Hiromi; Sasaki, Katsumi; Ariyoshi, Yuichi; Sadahira, Takuya; Araki, Motoo; Ebara, Shin; Yanai, Hiroyuki; Watanabe, Masami; Nasu, Yasutomo
Abstract: In a phase I/IIa study of in situ gene therapy using an adenovirus vector carrying the human REIC/Dkk‐3 gene (Ad‐REIC), we assessed the inhibitory effects of cancer recurrence after radical prostatectomy (RP), in patients with high risk localized prostate cancer (PCa). After completing the therapeutic interventions with initially planned three escalating doses of 1.0 × 10 10, 1.0 × 10 11, and 1.0 × 10 12 viral particles (VP) in 1.0–1.2 mL ( n = 3, 3, and 6), an additional higher dose of 3.0 × 10 12 VP in 3.6 mL ( n = 6) was further studied. Patients with recurrence probability of 35% or more within 5 years after RP as calculated by Kattan's nomogram, were enrolled. They received two ultrasound‐guided intratumoral injections at 2‐week intervals, followed by RP 6 weeks after the second injection. Based on the findings of MRI and biopsy mapping, as a rule, one track injection to the most prominent cancer area was given to initial 12 patients and 3 track injections to multiple cancer areas in additional 6 patients. As compared to the former group, biochemical recurrence‐free survival of the latter showed a significantly favorable outcome. Neoadjuvant Ad‐REIC, mediating simultaneous induction of cancer selective apoptosis and augmentation of antitumor immunity, is a feasible approach in preventing cancer recurrence after RP. (199)